(untitled) (Universal International Scientific Journal, 2026)
The article analyzes the components, content and impact of pedagogical competence on the effectiveness of education in the work of a teacher. The factors of development of pedagogical competence and its importance in the modern educational process are highlighted on the basis of scientific sources. It is shown that pedagogical competence is an important component of the professional competence of a teacher.